Fluorescent pattern recognition of metal ions by nanoparticles of bovine serum albumin as a chemical nose/tongue. Issue 19 (4th September 2020) - Fan, Yu-Lin; Lu, Yi-Fan; Ding, Xu-Yin; Wang, Nai-Hong; Xu, Feng; Shi, Guoyue; Zhang, Min
Abstract : A sensor array mimicking a chemical nose/tongue based on bovine serum albumin nanoparticles (BSANs n ) has been developed for the fluorescence pattern recognition of metal ions in biofluids. Abstract : A sensor array mimicking a chemical nose/tongue based on bovine serum albumin nanoparticles (BSANs n ) has been developed for the fluorescence pattern recognition of metal ions in biofluids. Three types of BSANs n (BSANs10, BSANs20, and BSANs40 ) show the same excitation/emission peak at 478/526 nm. According to the differential fluorescence variation, the sensor array shows particular fluorescence response patterns depending upon metal ions. Upon principal component analysis (PCA), it was found that the sensor array can distinguish 18 metal ions clearly at a concentration of as low as 10 μM. Moreover, different concentrations of metal ions and mixed metal ions of diverse kinds or valence states can be differentiated by the sensor in biofluids. In addition, the results were well consistent with those obtained with the traditional ICP-AES method.